Identification of a structural determinant for resistance to β-lactam antibiotics in Gram-positive bacteria - Mouz, N. (The National Academy of Sciences, 1998)
Streptococcus pneumoniae is the main causal agent of pathologies that are increasingly resistant to antibiotic treatment. Clinical resistance of S. pneumoniae to β-lactam antibiotics is linked to multiple mutations of high molecular mass penicillin-binding proteins (H-PBPs), essential enzymes involved in the final steps of bacterial cell wall synthesis. H-PBPs from resistant bacteria have a reduced affinity for β-lactam and a decreased hydrolytic activity on substrate analogues. In S. pneumoniae, the gene coding for one of these H-PBPs, PBP2x, is located in the cell division cluster (DCW). We present here structural evidence linking multiple β-lactam resistance to amino acid substitutions in PBP2x within a buried cavity near the catalytic site that contains a structural water molecule. Site-directed mutation of amino acids in contact with this water molecule in the “sensitive” form of PBP2x produces mutants similar, in terms of β-lactam affinity and substrate hydrolysis, to altered PBP2x produced in resistant clinical isolates. A reverse mutation in a PBP2x variant from a clinically important resistant clone increases the acylation efficiency for β-lactams and substrate analogues. Furthermore, amino acid residues in contact with the structural water molecule are conserved in the equivalent H-PBPs of pathogenic Gram-positive cocci. We suggest that, probably via a local structural modification, the partial or complete loss of this water molecule reduces the acylation efficiency of PBP2x substrates to a point at which cell wall synthesis still occurs, but the sensitivity to therapeutic concentrations of β-lactam antibiotics is lost.